Spatial Proximity Distribution of COVID-19 in Iran (Panel: February 2019-February 2023) - Afshin Mottaghi; Michael Aryan Kya (Iranian Journal of Medical Sciences, 2024)
Despite substantial advancements in disease management, contagious diseases continue to be important in epidemiology and public health.